5S – a quality improvement tool for sustainable performance: literature review and directions. Issue 3 (6th March 2017) - Randhawa, Jugraj Singh; Ahuja, Inderpreet Singh
Abstract : Purpose: The purpose of this paper is to present the comprehensive literature review on 5S and suggest possible gaps from the point of view of researchers and practitioners. The manuscript presents the overview of 5S implementation and highlights the achievements realized from deployment of 5S initiatives for sustainable performance of organizations. Design/methodology/approach: The paper critically examines the literature on 5S, analyzes and reviews it systematically. The study highlights the critical barriers and success factors for sustainable 5S implementation in the organizations in the competitive world. Findings: 5S is an outstanding Japanese philosophy for the development of any type organization all over the world. This study bring out the concept of 5S, requirements for its holistic implementation, relationship with other lean tools, benefits, success factors and obstacles in 5S implementation. The significant contributions through 5S initiatives in the organization like production, quality, safety and effective utilization of workspace for the sustained organizational improvement have also been highlighted in the study. Practical implications: The literature on assortment of 5S technique has been so far very limited. The present paper reviews large number of research publications related to 5S to highlight the significance of 5S philosophy in the sustainable organizational improvement across the world. It foregrounds the approach advised by the various researchers, practitioners and appraises censoriously the reason behind the demand of 5S program in the organization. The needful steps and obstacles are also foreground for the effective implementation of 5S in the organization. Originality/value: The paper presents a comprehensive review of literature publications in the area of 5S and their assortment to develop an understanding of the significance and implementation of 5S in the organizations. The paper will be helpful or useful to researchers, safety executives, development professionals and managers in the organizations.